Revealing Narratives in Before and After Photographs of Cosmetic Breast Surgeries - Hurst, Rachel Alpha Johnston (Imaginations, 2020)
Feminist cosmetic surgery scholars have been attentive to cosmetic breast surgeries as emblematic of a range of issues and questions. Breast implant and reduction surgeries have been analyzed by scholars as psychologically beneficial, as representative of unethical practices in the cosmetic surgery industry, as exemplar of the objectification of women’s bodies, and as connected to powerful cultural ideas about breasts. A curious dearth in previous scholarship is a sufficient engagement with the ubiquitous library of photographs that document these procedures. This essay discusses before and after photographs of cosmetic breast surgeries, which occupy a liminal space as medical and sexual, verification and fantasy. In this essay, I argue that before and after photographs of cosmetic breast surgeries should be read as revealing of the conditions under which patients and surgeons operate, rather than solely as proof of an operation’s results. To make this argument, I focus on two examples of before and after photographs – one of a breast augmentation and one of a breast reduction – and guide my analysis of the images in relation to narrative interviews with three women who underwent cosmetic breast surgeries.